Psychedelic Identity Shift: A Critical Approach to Set And Setting - Devenot, Neşe (Kennedy Institute of Ethics journal, 2022)
While the literature on psychedelic medicine emphasizes the importance of set and setting alongside the quality of subjective drug effects for therapeutic efficacy, few scholars have explored the therapeutic frameworks that are used alongside psychedelics in the lab or in the clinic. Based on a narrative analysis of the treatment manual and post-session experience reports from a pilot study of psilocybin-assisted treatment for tobacco smoking cessation, this article examines how therapeutic frameworks interact with the psychedelic substance in ways that can rapidly reshape participants' identity and sense of self. We identified multiple domains relating to identity shift that appear to serve as smoking cessation mechanisms during psilocybin sessions, each of which had an identifiable presence in the manualized treatment. As psychedelic medicine becomes mainstream, consensual and evidence-based approaches to psychedelic-assisted identity shift that respect patient autonomy and encourage empowerment should become areas of focus in the emergent field of psychedelic bioethics.